CDCA3 exhibits a role in promoting the progression of ovarian cancer. (December 2022) - Gong, Shan; Bai, Bo; Sun, Guangyu; Jin, Haihong; Zhang, Zhengmao
Abstract: Objective: Ovarian cancer (OC) is one of the common gynecological malignant tumors. Cell division cycle-associated protein-3 (CDCA3) is involved in the regulation of cell cycle progression. The role of CDCA3 in OC was explored in this study. Methods: The expression of CDCA3 in OC was evaluated in the Gene Expression Omnibus (GEO) database and further verified by qRT-PCR and Western blot (WB). Subsequently, we established lentivirus-mediated CDCA3 knockdown in OC cell lines HO-8910 and A2780. The biological roles of CDCA3 on proliferation, sensitivity to cisplatin, apoptosis, migration and tumor formation of OC were investigated using loss-of-function assays. Results: CDCA3 was frequently up-regulated in OC. Knockdown of CDAC3 inhibited proliferation and migration, and enhanced apoptosis as well as sensitivity of OC cells to cisplatin. In vivo results further confirmed the inhibitory effect of CDCA3 knockdown on tumor growth. Conclusions: Our findings indicated that CDCA3 may play an important role in OC progression, and may serve as a potential therapeutic target for the OC treatment. Highlights: CDCA3 was frequently up-regulated in ovarian cancer. CDCA3 knockdown could potently inhibit ovarian cancer cell progression in vitro . CDCA3 Knockdown could efficiently suppress tumor growth of ovarian cancer in vivo . CDCA3 may be a potential molecular therapy target for ovarian cancer treatment.